2015
DOI: 10.1016/j.bej.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Efficient P(3HB) extraction from Burkholderia sacchari cells using non-chlorinated solvents

Abstract: A technique for poly-3-hydroxybutyrate (P(3HB)) extraction with safer, non-chlorinated solvents, was developed, aiming to attain high recovery yields and purities. A wide range of solvents was selected from the GlaxoSmithKline guide as sustainable industrial solvents and the solubility of P(3HB) on those solvents calculated using predictive equations from literature. Anisole, * Corresponding author: Tel.: +351 21 8419137; Fax: +351 21 8419062. e-mail address: teresa.cesario@tecnico.ulisboa.pt + Current address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 36 publications
(48 reference statements)
3
32
0
Order By: Relevance
“…The MW obtained in the present study are within the range of the molecular weights reported in the literature (1.0 × 10 4 Da -4.0 × 10 6 Da). However, 10 5 Da are the lowest molecular weights described for PHA biopolymers (Fiorese et al, 2009;Rosengart et al, 2015). Furthermost of the molecular weight, the PDI is of great importance since it is going to be an indicator of the homogeneity of a copolymer.…”
Section: Molecular Weightmentioning
confidence: 99%
“…The MW obtained in the present study are within the range of the molecular weights reported in the literature (1.0 × 10 4 Da -4.0 × 10 6 Da). However, 10 5 Da are the lowest molecular weights described for PHA biopolymers (Fiorese et al, 2009;Rosengart et al, 2015). Furthermost of the molecular weight, the PDI is of great importance since it is going to be an indicator of the homogeneity of a copolymer.…”
Section: Molecular Weightmentioning
confidence: 99%
“…Several methods have been reported for the extraction of P(3HB) from the biomass of different organisms, and although these procedures are known to offer promising results, there are still obstacles for the efficient recovery of the biopolymer. Several studies in the literature have reported the use of nonhalogenated solvents . Most of these reports used polar or semi‐polar compounds, to solubilize nonpolar hydrophobic compounds, such as PHAs; therefore, in most of these studies it was necessary to use high temperatures (120–150 °C), as well as high pressures to improve the plastic extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies in the literature have reported the use of nonhalogenated solvents. 6,[35][36][37] Most of these reports used polar or semi-polar compounds, to solubilize nonpolar hydrophobic compounds, such as PHAs; therefore, in most of these studies it was necessary to use high temperatures (120-150 ∘ C), as well as high pressures to improve the plastic extraction. The above implies a high energy consumption, affecting the costs of polymer separation.…”
Section: Separation and Purification Of The P(3hb) Obtained At Pilot mentioning
confidence: 99%
“…Jung et al [103] manipulated the initial inoculum size and the composition of the medium and obtained an Escherichia coli strain that was able to produce PHB at a very high fraction [103]. After spontaneous cell lysis, PHB granules were released into the medium; • Extraction of PHB using non-chlorinated solvents (e.g., anisole) [104] or non-halogenated solvents (e.g., butyl acetate) [105]; • Extraction of PHB with a solvent-free approach using enzyme digestion in an aqueous medium [106]. Martino et al [106] used biomass of Cupriavidus necator DSM 428 grown on used cooking oil (UCO) for extraction of the PHB granules using sodium dodecyl sulphate (SDS), ethylenediaminetetraacetic acid (EDTA), and the enzyme alcalase in an aqueous medium.…”
Section: Phb Recoverymentioning
confidence: 99%